Evaluation of Organic Substrates for Outdoor Cultivation of Pleurotus Tuber-Regium - Olutayo M, Adedokun; Juliet N, Friday (The International Journal of Biotechnology, 2020)
Pleurotus tuber-regium is a unique mushroom with a lot of benefits. Yield of the mushroom was evaluated when cultivated outdoor on agricultural beds different substrates (treatments) in order to assess the effect of the substrates. Four substrates used were topsoil, a mixture of topsoil and sawdust (2kg), a mixture of topsoil and poultry droppings (2kg), and a mixture of topsoil, poultry droppings (2kg) and sawdust (2kg). The design was Randomized Complete Block Design (RCBD) with four replicates. Results showed that mixture of topsoil and sawdust had the highest mean dry weight 3.54±0.29 for first flush while the least was 2.57±0.45gm for topsoil. For the second flush, the highest mean dry weight of 1.56±0.37 was for mixture of topsoil and sawdust while the least, 0.58±0.31gm was for topsoil, poultry droppings and sawdust. Results for dry weight of fruiting bodies, indicated that only the mixture of Topsoil & Poultry droppings and Topsoil, Poultry droppings & Sawdust had no significant difference (P>0.05), for first flush; there was significant difference between other treatments. Results for second flush had no significant difference (P>0.05) between Topsoil and Topsoil & Sawdust treatments; there was significant difference (P<0.05), between other treatments. There was significant difference (P<0.05) in the stipe girth, pileus diameter and wet weight for all the treatments for both flushes. Significant difference between treatments varied for stipe height. The mixture of topsoil and sawdust substrate is recommended for the outdoor cultivation of Pleurotus tuber-regium. These findings are discussed.